Crater Morphometry on the Mafic Floor Unit at Jezero Crater, Mars: Comparisons to a Known Basaltic Lava Plain at the InSight Landing Site. Issue 17 (25th August 2020) - Warner, Nicholas H.; Schuyler, Andrew J.; Rogers, A. Deanne; Golombek, Matthew P.; Grant, John; Wilson, Sharon; Weitz, Cathy; Williams, Nathan; Calef, Fred
Abstract: A secondary objective for the Perseverance rover mission to Jezero crater, Mars, is to collect igneous rocks for analysis on Earth. The mafic crater floor unit (MFU) represents the best candidate. Ten‐meter‐scale craters on the MFU exhibit rocky ejecta, rims, and slopes that indicate resistant rock. The frequency distribution of these craters is, however, low. Comparisons of MFU craters to craters on a lava plain at the Interior Exploration using Seismic Investigation, Geodesy and Heat Transport mission (InSight) landing site reveal that the MFU lacks a granular regolith. Removal of regolith or exhumation of the MFU explains the rocky crater morphology and low density. Erosion rates, calculated using crater retention timescales of ~2.0 Ga for both locations, are 10 −3 to 10 −4  m/Myr. The rates derive from craters impacted into rocky materials on the MFU versus regolith at InSight. The difference in material strength, yet comparable erosion rates, requires more vigorous surface processes at Jezero relative to global averages on Mars. Plain Language Summary: Jezero crater is a 45‐km diameter impact crater on Mars. It contains a river delta and deposits that suggest that it was once filled by a lake. Jezero is the landing site for NASA's Mars Perseverance rover, scheduled to land in February 2021. A primary objective of the rover is to sample rocks to determine if Mars was once habitable for life. A secondary objective is to obtain igneous rocks, or rocks that crystallize from magma or lava. Igneous rocks can be used to provide absolute age constraints on the rocks that they surround or are contained within. The purpose of this study is to evaluate a geologic unit called the mafic floor unit that is the best candidate for sampling igneous material. Small craters that formed from meteor impacts in the floor unit are surrounded by large rocks that suggest that the material is resistant to weathering and erosion, consistent with craters impacted into hard igneous rocks or other competent material. However, the unit lacks a sand‐sized surface soil that is typical of most lava plains on Mars. Comparisons to the InSight landing site indicate that wind may be responsible for removing sandy material and exposing rock. Key Points: The mafic floor unit at Jezero crater is a morphologically resistant unit The mafic floor unit at Jezero crater lacks a granular surface regolith like other lava plains on Mars Surface processes operate at relatively higher rates within Jezero crater compared to global averages on Mars